Temporomandibular Disorders Related to Stress and HPA-Axis Regulation - Kordian Staniszewski; Henning Lygre; Ersilia Bifulco; Siv Kvinnsland; Lisa Willassen; Espen Helgeland; Trond Berge; Annika Rosén (Pain Research and Management)
Temporomandibular disorders (TMDs) are characterized by pain and dysfunction in the masticatory apparatus and the temporomandibular joint (TMJ). Previous trauma, stress symptoms, psychosocial impairment, and catastrophizing have been related to TMD. To assess if the hypothalamic-pituitary-adrenal (HPA) axis is upregulated in TMD patients, we performed a cross-sectional study with saliva from 44 TMD patients and 44 healthy sex- and age-matched controls for cortisol (F) and cortisone (E) with liquid chromatography-tandem mass spectrometry. Furthermore, we calculated the F/E ratio for the evaluation of 11β-hydroxysteroid dehydrogenase activity. We also assessed anxiety/depression and pain catastrophizing scores from a questionnaire that participants completed prior to the examination. We found that F (P=0.01), E (P=0.04), the F/E ratio (P=0.002), and the sum of glucocorticoids (E + E) in saliva (P=0.02) were significantly higher in the TMD group. Anxiety/depression and catastrophizing scores were also significantly higher in the TMD group (P<0.0001). Our findings indicate that patients with TMDs may have an upregulated HPA axis with higher F secretion from the adrenal cortex. Anxiety/depression and pain catastrophizing scores were significantly higher in the TMD group, and psychological factors may contribute to chronic upregulation of the HPA axis.